Factors Associated with Parental Compliance in Providing Basic Immunization to Children - Agustini, Elina; Nurvinanda, Rezka; Agustin, Agustin (Genius Journal, 2025)
Introduction: Basic immunization is a series of vaccines given to infants and children from an early age (from birth to 0-24 Months), to stimulate the immune system to form antibodies against certain diseases. This basic immunization is mandatory as a primary preventive measure against infectious diseases such as tuberculosis (BCG), hepatitis B, polio, diphtheria, pertussis (whooping cough), tetanus and measles. Objective: The general objective of this study is to determine the factors associated with parental compliance in providing basic immunizations to children in the Lubuk Besar Community Health Center work area in 2025. Method: The type of research used is quantitative with the research design used being descriptive analytical through an approach Cross Sectionalnamely conducting a cross tab between the dependent variable and the independent variable. The sample in this study were parents who had children aged 0-24 Months as many as 74 people. Data analysis using the testwho squareswith a confidence level of 95%. Result: The results of the study are to find out between the dependent variable, namely parental compliance in providing basic immunization to children and the independent variables consisting of maternal age, employment status, knowledge and family support. The results of the statistical test of the maternal age variable obtained a value of p = 0.009, the employment status variable obtained a value of p = 0.029, the knowledge variable obtained a value of p = 0.002 and the family support variable obtained a value of p = 0.005. Conclusion: It is recommended to improve ongoing education through counseling, information media and direct counseling to parents about the importance of basic immunization for children, as well as facilitating access to immunization services with flexible schedules and easily accessible locations to improve parental compliance.